The Magician's Elephant - Kate DiCamillo (Candlewick Entertainment, 2023)
When a fortuneteller's tent appears in the market square of the city of Baltese, orphan Peter Augustus Duchene knows the questions that he needs to ask: Does his sister still live? And if so, how can he find her? The fortuneteller's mysterious answer (an elephant! An elephant will lead him there!) sets off a chain of events so remarkable, so impossible, that you will hardly dare to believe it's true. With atmospheric illustrations by fine artist Yoko Tanaka, this timeless fable from Kate DiCamillo evokes the largest of themes--hope and belonging, desire and compassion--with the lightness of a magician's touch.
Keywords: Fantasy -- Fantasy